2018
DOI: 10.3390/ijerph15040667
|View full text |Cite
|
Sign up to set email alerts
|

‘We All Work Together to Vaccinate the Child’: A Formative Evaluation of a Community-Engagement Strategy Aimed at Closing the Immunization Gap in North-West Ethiopia

Abstract: The role of community engagement (CE) in improving demand for immunization merits investigation. The International Rescue Committee developed a CE strategy to implement a vaccine defaulter-tracing tool and a color-coded health calendar aimed at increasing uptake of immunization services in north-west Ethiopia (‘The Fifth Child Project’). We report findings from a formative evaluation of this project. In May/June 2016 we conducted 18 participant observations of project activities, 46 semi-structured interviews … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
2

Relationship

3
3

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 16 publications
0
13
0
Order By: Relevance
“…Nearly 54% of all eligible infants in both woredas defaulted at least once during the project period. Involvement of caregivers in mining activities and associated travels were reported to the study team as one of the key causes for default [ 13 ]. Nonetheless, most defaulters (84%) were identified and subsequently caught up with vaccinations they had missed, exceeding the 70% target.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Nearly 54% of all eligible infants in both woredas defaulted at least once during the project period. Involvement of caregivers in mining activities and associated travels were reported to the study team as one of the key causes for default [ 13 ]. Nonetheless, most defaulters (84%) were identified and subsequently caught up with vaccinations they had missed, exceeding the 70% target.…”
Section: Discussionmentioning
confidence: 99%
“…We conducted an evaluation, consisting of quantitative and qualitative methods, to assess FCP contribution in improving utilization of immunization and related perinatal services in BGRS. This paper describes the intervention and reports quantitative findings; qualitative methods and findings are presented in a complementary paper [ 13 ].…”
Section: Methodsmentioning
confidence: 99%
“…Interventions that promote joint decision making may be successful. An intervention supported by the IRC in Ethiopia assessed the impacts of the use of a color-coded health calendar to increase uptake of immunisation services and found that the calendar promoted health discussions within households (34). DHS data also indicate that women in BGRS have lower rates of FP use than women in almost every other region in the country (35).…”
Section: Perceptions Of Key Actorsmentioning
confidence: 99%
“…Significant emphasis is placed on promoting shared individual, community and governmental responsibility for immunization against vaccine preventable diseases in the Global Vaccine Action Plan (30). Projects that seek to engender shared responsibility for vaccination can however result in unexpected by-products, as was the case in a community engagement immunization project in north-west Ethiopia (31). Active engagement of health development army members and kebele (smallest administrative unit in Ethiopia) leaders in promoting immunization resulted in action that was not planned by the project implementers.…”
Section: Rural Area In Ethiopia: Promoting Shared Responsibility For mentioning
confidence: 99%
“…This community action is interesting in that it is decided at a more local level rather than imposed by higher levels of the health ministry or government. To what extent it was completely democratic is up for question, but the research findings suggested that the sanctions were endorsed by a variety of community members and suggested by members of the health development army who work closely with mothers in neighbouring households (31). Hence, although this community self-regulating exercise did give rise to questions about the coercion and individual rights, it encroached less on civil liberties in that the sanctions were agreed in keeping with pre-existing community accountability mechanisms, which involve community members and representatives.…”
Section: Rural Area In Ethiopia: Promoting Shared Responsibility For mentioning
confidence: 99%